Optimal channel transmission of Gaussian Markov signal with delay; Control and Communications (SIBCON) - Rozhkova S. V. Svetlana Vladimirovna; Rozhkova V. I. Valentina Ivanovna; Lasukov V. V. Vladimir Vasilievich; Devyashina E. V. (2016, 2016)
Title screen